أزمة علمية شرعية للمجتمع النسائي في بنغلاديش: أسباب وعلاج - Syed Mahmudul Hasan (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2019)
This study aims to disclose the crisis of Women in Bangladesh in the area of Islamic Knowledge and Science. It further studies the reason behind this and its negative impact on their daily life. The researcher discussed and interviewed from the Bangladeshi prominent scholars to overcome this crucial situation. The methodology adopted in this study is the inductive approach to describe an inclusive overview of Bangladeshi Women’s daily life and their involvement and contribution in every spare of living. And the analytical interview approach to analyze their crisis of Islamic Knowledge, by defining the reasons behind this and how that influence their way of living. Then follow scholarly opinions on that issue to come to a productive solution. The study arrived at the results that the only relief from this crisis is to open all way of learning Islam for them, most importantly the Mosque, then they can interest to know the beauty of Islam and join to exercise the voluntary task for betterment of the Society.